Analysis Implementation of The Stunting Prevention Programme - Mira Ulpayani Harahap; Rapotan Hasibuan (Journal of Health Science and Prevention, 2023)
Stunting is one of the health issues that has become a major concern for the government in Indonesia. The term stunting refers to a condition where a toddler has a lower height compared to the size that should be appropriate for his or her age. The standard used to determine stunting is a height measurement that is lower than two standard deviations below the median of children's growth standards set by the World Health Organization (WHO). The purpose of this study is to analyse how the implementation of the stunting prevention program is carried out by the health sector in the UPTD Puskesmas Gunung Tua to find out the description of the problems and provide recommendations that may be done to improve the stunting prevention program. Methods: This research used a qualitative approach with a case study design at the UPTD Puskesmas Gunung Tua. The research was conducted from December 2022 to July 2023. The data used were primary data collected through in-depth interviews with informants, the Head of Puskesmas, the holder of the stunting program, nutrition cadres, midwives, and people who have stunted babies, with semi-structured interview guidelines. Secondary data was obtained from monthly reports provided by nutrition cadres, midwives, and the community, who have stunted babies, with semi-structured interview guidelines, while secondary data was obtained from monthly reports provided by Health cadres. Results: This study found that the stunting programme has been running smoothly but in these activities, there are still some obstacles encountered, lack of resources from the puskesmas.